Experimental Study on Reasonable Horizontal Load Value on the Top of Railings of Glass Bridges or Gallery Roads in Scenic Area. (6th August 2021) - Sun, Qingwen; Yan, Qiushi; Liu, Liqu; Wang, Haowei
Abstract : With the increase of glass bridges or glass walkways in the scenic area, the safety protection provided by railings cannot be neglected. However, there is a difference between the demands for a horizontal load on the top of railings in the present design specifications. Especially, it does not give specific advice on the horizontal load on the top of railings of glass bridges or glass roads in the scenic area. In this study, experimental research is conducted on railing columns based on the investigation of common railings of glass bridges or glass roads in the scenic area. The type of railing columns includes finished products and field production. The number of railing columns is 12. The displacement and strain results of the railing columns under different loads are obtained. The rigidity and strength are analyzed by numerical simulation combined with test results. A reasonable horizontal load on the top of the railings of a glass bridge or glass road is advised. These results provide a reference for the design, inspection, and evaluation of railings of glass bridges or gallery roads in the scenic area.